2013
DOI: 10.1073/pnas.1315458110
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse, parental warmth, and adult multisystem biological risk in the Coronary Artery Risk Development in Young Adults study

Abstract: Childhood abuse increases adult risk for morbidity and mortality. Less clear is how this "toxic" stress becomes embedded to influence health decades later, and whether protective factors guard against these effects. Early biological embedding is hypothesized to occur through programming of the neural circuitry that influences physiological response patterns to subsequent stress, causing wear and tear across multiple regulatory systems. To examine this hypothesis, we related reports of childhood abuse to a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
160
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(171 citation statements)
references
References 56 publications
9
160
1
1
Order By: Relevance
“…Additionally, remembrances of parental acceptance in childhood have been shown to be an overall buffer in adulthood against the development of biomarkers indicating a proneness for many negative physical-health outcomes such as cardiovascular disease (Carroll et al, 2013).…”
Section: Quantitative Psychological Studiesmentioning
confidence: 99%
“…Additionally, remembrances of parental acceptance in childhood have been shown to be an overall buffer in adulthood against the development of biomarkers indicating a proneness for many negative physical-health outcomes such as cardiovascular disease (Carroll et al, 2013).…”
Section: Quantitative Psychological Studiesmentioning
confidence: 99%
“…Lately, epidemiological studies have shown that ACEs were associated with mortality and health even after adjusting for socioeconomic and behavioral factors, suggesting that a direct biological effect occurring from early life is plausible (28,29). It has been suggested that psychosocial factors could protect and buffer early adverse circumstances, such as parental warmth and psychological resources, reducing physiological responses and mitigating disease processes (30,31). However, only a few studies have analyzed the influence of ACE on health over the life course by examining these different pathways, and fewer have used an AL index.…”
Section: Significancementioning
confidence: 99%
“…This relationship was confirmed in subsequent studies and extended to a variety of developmental stressors. Children raised in low socioeconomic status families under harsh and stressful conditions predicted increasing blood pressure (BP) over time and increased vascular reactivity to stress [CARDIA study (9,34), reviewed in Ref. 56].…”
Section: There Is Increasing Interest In Developmental Programming Ofmentioning
confidence: 99%